The pressure response of SnSxSe2-x tin dichalcogenide alloys studied by Raman spectroscopy - Sorogas, Niki; Menelaou, Melita; Anagnostopoulos, A. N.; Papagelis, Konstantinos; Christofilos, Dimitris; Arvanitidis, John (My University, 2023)
High-pressure Raman spectroscopic experiments were conducted in a diamond anvil cell to investigate the pressure response of the phonon modes of SnSxSe2-x (x = 0.6, 0.8, 1) tin dichalcogenide alloys up to 8 GPa. Owing to the two-mode behavior of the Eg and A1g modes in these ternary alloys, up to four Raman bands are observed at ambient conditions and the frequency evolution of three of them {Eg(SnSe2-like), A1g(SnSe2-like) and A1g(SnS2-like)} is followed with pressure. With increasing pressure, all the Raman bands shift quasi-linearly and reversibly to higher frequencies, reflecting the bond stiffening due to the volume reduction and the absence of any phase transition. Despite the stronger intralayer covalent bonding compared to the much weaker interlayer van der Waals interactions along the c-axis, the in-plane Eg(SnSe2-like) mode has larger pressure coefficient than those of the two stronger in intensity A1g modes along the c-axis. The pressure coefficient of the A1g(SnS2-like) mode gradually increases from 3.60 to 3.93 cm−1GPa−1 with increasing sulfur content (x). On the other hand, the pressure coefficient of the A1g(SnSe2-like) mode decreases from 3.08 to 2.72 cm−1GPa−1 with increasing x. The extracted Grüneisen parameters of all the A1g Raman peaks indicate the stronger Sn–S interaction along the c-axis compared to that of Sn–Se.
Keywords: 2D materials; High pressure; Raman spectroscopy; Tin dichalcogenide alloys